Impaired CD27+IgD+ B Cells With Altered Gene Signature in Rheumatoid Arthritis - Hu, Fanlei; Zhang, Wei; Shi, Lianjie; Liu, Xu; Jia, Yuan; Xu, Liling; Zhu, Huaqun; Li, Yingni; Xu, Dakang; Lu, Liwei; Qiu, Xiaoyan; Liu, Wanli; et al. (Frontiers in Immunology, 2018)
Natural antibodies, particularly natural IgM, are proved to play indispensable roles in the immune defenses against common infections. More recently, the protective roles of these natural IgM were also recognized in autoimmune diseases. They are mainly produced by B-1 and innate-like B cells (ILBs). Human CD19+CD27+IgD+ B cells, also termed as un-switched memory B cells, were proposed to be a kind of ILBs. However, functional features and characteristics of these cells in rheumatoid arthritis (RA) remained poorly understood. In this study, we found that human CD27+IgD+ B cells could produce natural antibody-like IgM. Under RA circumstance, the frequencies of these cells were significantly decreased. Moreover, the IgM-producing capacities of these cells were also dampened. Interestingly, the BCR repertoire of these cells was altered in RA, demonstrating decreased diversity with preferential usage alteration from VH3-23D to VH1-8. Single cell sequencing further revealed the proinflammatory biased features of these cells in RA. These CD27+IgD+ B cells were negatively correlated with RA patient disease activities and clinical manifestations. After effective therapy with disease remission in RA, these cells could be recovered. Taken together, these results have revealed that CD27+IgD+ B cells were impaired in RA with dysfunctional features, which might contribute to the disease perpetuation.